Abundância e atividade metabólica da microbiota do solo da rizosfera de gramíneas nativas e invasoras em áreas de cerrado na Estação Ecológica de Itirapina, SP - Pierozzi, Mayara (2017)
Biological invasions are considered the second major cause of biodiversity losses and invasions by exotic grasses constitute one of the most severe cases of invasions in native plant formations, intensely modifying ecosystems functioning. Invasive species change important ecosystem processes such as nutrient cycling, decomposition and fire regimes. According to some authors invasive grasses can alter soil microorganisms, in such way that these become a facilitator to their establishment. This study aimed to compare the abundance and metabolic activity of soil microbiota in the rhizosphere of invasive and native grasses. The research was carried out in the Ecological Station of Itirapina, São Paulo, in four areas being two in “campo cerrado” and two in “campo sujo” plant formation. Two samplings were carried out in the year 2015, one in March, at the end of rainy season and other in September at the end of the dry season. Abundance of microorganisms (bacteria, fungi and protozoans), carbon (C) and nitrogen (N) content in the microbial biomass were quantitatively determined in the soil of the rhizosphere of three species of native (Loudetiopsis chrysothrix, Tristachya leiostachya, e Panicum sp.) and three species of invasive grasses (Melinis minutiflora, Melinis repens e Urochloa decumbens). The metabolic activity (microbial respiration) was measured and a metabolic quotient calculated as an indicator of the efficiency of carbon incorporation into microbial biomass. Physical and chemical characteristics of soil in the rizosphere of all species of grass studied were measured: granulometric soil fractions, temperature, pH, humidity, total C, N, and organic matter concentrations. Significant differences were found when comparing the soil from the rhizosphere of invasive and native grasses in both “campo cerrado” and “campo sujo” formations regarding Fungi density, total carbon and total N in the microbial biomass, total organic C and N in the soil and metabolic quocient. Values of carbon and nitrogen in microbial biomass and also total organic C and N in the soil were higher in native species than in invasive ones. Metabolic quotient values showed high values for invasive than for native grass species, thus indicating that the microbiota in the rhizosphere of invasive species has lower efficiency of carbon incorporation into their biomass, what appears to be a consequence of changes in the rhizosphere of exotic invasive grasses.